2021
DOI: 10.1093/eurheartj/suab140.051
|View full text |Cite
|
Sign up to set email alerts
|

448 Comparison of quantitative flow ratio, Pd/Pa, and diastolic hyperaemia-free ratio vs. fractional flow reserve in non-culprit lesion of patients with non-ST-segment elevation myocardial infarction

Abstract: Aims To investigate the correlation between quantitative flow ratio (QFR), Pd/Pa, diastolic hyperaemia-free ratio (DFR), and fractional flow reserve (FFR, gold standard) in non-culprit lesion (NCL) of patients with non ST-segment elevation myocardial infarction (NSTEMI). The non-hyperemic pressure ratio (NHPR) and the angiography-based indexes have been developed to overcome the limitation of the use of the FFR. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Addressing this problem, our study investigates whether QFR guidance provides a better estimate of the severity of non-culprit lesions compared with angiography. Of importance, Tebaldi et al recently reported that QFR, Pd/Pa and DFR are equivalent to the gold standard FFR in the discrimination of non-culprit lesions requiring revascularization in patients with NSTEMI who have received PCI of all culprit lesions ( 18 ). Our study tests the hypothesis that QFR could provide a better stratification of patients/lesions requiring PCI for non-culprit lesions as compared to angiography, leading to more accurate identification of lesions requiring PCI and to reduced angina during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addressing this problem, our study investigates whether QFR guidance provides a better estimate of the severity of non-culprit lesions compared with angiography. Of importance, Tebaldi et al recently reported that QFR, Pd/Pa and DFR are equivalent to the gold standard FFR in the discrimination of non-culprit lesions requiring revascularization in patients with NSTEMI who have received PCI of all culprit lesions ( 18 ). Our study tests the hypothesis that QFR could provide a better stratification of patients/lesions requiring PCI for non-culprit lesions as compared to angiography, leading to more accurate identification of lesions requiring PCI and to reduced angina during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The area under the summary receiver operating characteristic (sROC) curve for QFR was 0.94 ( 13 ). Further, QFR has been validated by several studies in the context of non-culprit lesions of ACS ( 14 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though non-hyperaemic indices are an attractive solution for assessing physiological significance, a less invasive option would be the avoidance of wire-based techniques and QFR has emerged as one potential technology to address this problem. The technology is well-validated in patients without aortic stenosis (20)(21)(22)(23)(24), including in patients with myocardial infarction (24)(25)(26), and growing evidence is building for its validation in aortic stenosis (27,28). With this as a background, the present compared the diagnostic performance of QFR against not only FFR, but also multiple non-hyperaemic indices (iFR, dPR and Pd/Pa) in the setting of severe aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…QFR demonstrated an excellent discriminatory power to predict functionally significant FFR (AUC =0.92; 95% CI: 0.84 to 1.00; P<0.001) (Figure 3A) with good diagnostic Family history of IHD 9 [26] Previous MI, n (%) 4 [11] Previous CVA or TIA, n (%) 4 [11] Peripheral vascular disease, n (%) 1 [3] Atrial fibrillation, n (%) 4 [11] Chronic kidney disease, n (%) 3 [9] Echocardiographic parameters Diagonal artery 5 [9] Ramus intermedius artery 1 [2] Left circumflex artery 5 [9] Obtuse marginal artery 9 [16] Right coronary artery 3 [5] Posterior descending artery 3 [5] performance [sensitivity, 73%, specificity 91%, positive predictive value (PPV) 84%, negative predictive value (NPV) 84%, accuracy 84%] (Tables 3,4). QFR demonstrated similar diagnostic performance to iFR (difference in AUC =0.04; 95% CI: −0.04 to 0.12; P=0.…”
Section: Diagnostic Performance Of Qfrmentioning
confidence: 99%
“…Furthermore, QFR, as a research tool, can be computed both offline and online, allowing clinicians to wildly review available angiograms from a functional perspective. With these advantages, accumulating studies have investigated the diagnostic value of QFR for the functional assessment of NCL in ACS (Table 3) (26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Validation Studies Of Qfr In Acsmentioning
confidence: 99%